Megaprojects—mega failures? The politics of aspiration and the transformation of rural Kenya - Detlef Müller-Mahn; Kennedy Mkutu; Eric Kioko (The European Journal of Development Research, 2021)
Megaprojects are returning to play a key role in the transformation of rural Africa, despite controversies over their outcome. While some view them as promising tools for a 'big push' of modernization, others criticize their multiple adverse effects and risk of failure. Against this backdrop, the paper revisits earlier concepts that have explained megaproject failures by referring to problems of managerial complexity and the logics of state-led development. Taking recent examples from Kenya, the paper argues for a more differentiated approach, considering the symbolic role infrastructure megaprojects play in future-oriented development politics as objects of imagination, vision, and hope. We propose to explain the outcomes of megaprojects by focusing on the 'politics of aspiration', which unfold at the intersection between different actors and scales. The paper gives an overview of large infrastructure projects in Kenya and places them in the context of the countrys national development agenda 'Vision 2030′. It identifies the relevant actors and investigates how controversial aspirations, interests and foreign influences play out on the ground. The paper concludes by describing megaproject development as future making, driven by the mobilizing power of the 'politics of aspiration'. The analysis of megaprojects should consider not only material outcomes but also their symbolic dimension for desirable futures.
Keywords: 330; Politics of aspiration; Megaproject; Development corridor; Rural transformation; Kenya